Antibiotic resistance in East Asia: current status, risks, and response strategies - Zhang, Jiuding; Fan, Jinghua; Li, Dongfang; Yang, Caiping; Cheng, Ziqi; Cheng, Zihan; Qu, Hongmei; Li, Guoliang; Yuan, Ning; Song, Taixian; Zhou, Kaichun; Zhao, Yumin; et al. (The Journal of Infection in Developing Countries, 2026)
Introduction: This study investigates the current status and regional disparities of resistance to novel antibiotics in East Asia, exploring links to socioeconomic factors and identifying high-risk resistance determinants. Methodology: Metagenomic sequencing was performed on 1024 human fecal samples (25 local, 999 public) from 12 regions across China and Japan. Antibiotic resistance genes (ARGs) were identified by aligning sequences against a comprehensive antibiotic resistance database, focusing on 8 novel antibiotic classes. The relationship between regional per capita GDP and resistance rates for clinically relevant novel antibiotics was statistically analyzed. Results: Significant regional variation in resistance rates was observed for clinically used novel antibiotics (aminocoumarins, glycylcyclines, oxacephems, oxazolidinones, pleuromutilins). A significant inverse correlation was found between per capita GDP and resistance rates for aminocoumarins, glycylcyclines, and oxacephems, particularly pronounced within inland regions. Oxacephem resistance was alarmingly high (> 55% in all regions, > 90% in some). Oxazolidinone resistance remained low (< 28%). Pleuromutilin resistance showed a strong negative GDP correlation only inland. Analysis revealed 24 high-frequency ARGs (5 exceeding 45% coverage: CfxA, IsaB, MexB, abeS, IsaE). Minimal shared resistance determinants existed among novel antibiotic classes, except between oxazolidinones and pleuromutilins. Conclusions: Resistance to novel antibiotics in East Asia exhibits significant regional heterogeneity, strongly influenced by local economic development levels. Resistance rates for specific agents (e.g., oxacephems) critically limit their clinical utility, necessitating mandatory susceptibility testing. High-frequency ARGs linked to traditional antibiotic misuse pose cross-resistance risks. Surveillance and stewardship strategies must be regionally tailored, prioritizing vulnerable areas and tracking critical resistance loci for novel agents.